Management of Drinking Water and Sanitation Services; Accessibility and its Impact on Service Quality, Peru 2025 - Fernando Jaime Perry Lavado, Pablo; Cajavilca Lagos, Wilder Oswaldo (International Journal of Aquatic Research and Environmental Studies, 2026)
The purpose of this research is to verify how the variables "Management of drinking water and sanitation services and Accessibility to drinking water and sanitation services", affect the dimensions of the variable "Quality of water and sanitation services Enel Peru 2025. The research has a quantitative, cross-sectional, non-experimental, basic and correlational descriptive approach. Among the main results, it can be mentioned that in Peru in 2025 there are 4.07 million inhabitants without access to safe water and 9.8 million inhabitants without quality sewerage or sanitation, deteriorating the quality of life and affecting the health and exposure to risk of this human group. On the other hand, economic and financial indicators show that there are deficiencies, which is why there are 19 providers intervened by OTASS. And in relation to quality, it can be seen that most of them are discontinuous systems, with excess water losses, and lack of effective metering, with infrastructure that already requires renovation, a high level of complaints and a low level of effective treatment of wastewater. Among the main recommendations is that the state should be concerned with generating new and trained personnel to take over the reins of companies and improving salary levels to attract trained and experienced professionals who can show results in the short term. In relation to accessibility, it is recommended to reformulate procedures to promote and expedite investment, given that billions are required to close gaps in accessibility and renovation of infrastructure, as well as institutional projects. In general, it is indicated that the main problem facing the drinking water and sanitation sector is the inability to execute investments with quality and efficiency.
Keywords: Management, Accessibility and Quality, Sanitation Services